Tawid-Dagat : Pag-ugat sa Maritimong Nakaraan ng Pilipino, 67,000 t.n.-900 MK - Isorena, Efren B. (Philippine Social Sciences Review, 2014)
Sea-crossing is considered among the thresholds in the complex development of modern humans. Evidence of early sea-crossings are to be found east of the Huxley-Wallacea Line, an area that remained surrounded by deep and wide sea even during periods of glaciation, thus, any evidence of human presence in the area would presume sea crossing. So far the earliest evidence suggesting sea-crossing east of the Huxley-Wallacea Line is to be found in the Philippines with an estimated date of 67,000 BP. This and the suggestion that the Philippines was launching ground for Austronesian expansion beginning in c.a. 5,000 BP underscores its significant role in the early development of maritime culture in general, and the boat culture in particular. The Philippine maritime past has a deep and long history which could provide us with some insights on questions regarding Filipino origin and identity. According to present evidence, hunter-gatherer founding populations reached the archipelago through rafts drifting according to sea and wind current directions which persisted throughout the Pleistocene. By the Holocene, Neolithic population, speaking the Austronesian language, in controlled navigation using dugout boats began a series of migration in the archipelago establishing sedentary coastal and riverine settlements and introducing food production through agriculture. The Late Holocene until the introduction of iron saw the establishment of a wide and systematic foreign maritime trade network conducted in the hulls of plank-built boats that would usher in the emergence of early ethnic states in the Philippines beginning in 900 AD.